Grete Samsa’s Inconsistent Speech. Victimary Lies and Distortions in Kafka’s "Die Verwandlung" - Bermejo-Rubio, Fernando (Revista de Filología Alemana, 2012)
In the third part of Die Verwandlung, Grete Samsa delivers a violent speech inciting her parents to get rid of Gregor. This speech contains the most explicit categorisation of the central character as “animal” and “monster”. Given that most scholars think that Kafka tells the metamorphosis of a man into a monstrous vermin, they assume that Grete’s words are (at least partially) trustworthy. A careful analysis of this speech, however, surprisingly reveals that it is full of lies, slander, distorted reasoning and even a parapraxis. Furthermore, it contains a set of fallacies which reproduce each and every one of the distortions which take place within a victimary circle. Hence, Grete’s speech (including her description of Gregor as an “animal”) is wholly inconsistent and unreliable. This conclusion makes the other categorisations designating Gregor as non-human suspicious, and provides a further argument proving that the prevailing interpretation of Die Verwandlung as a metamorphosis story is disturbingly misguided.